APPARATUS FOR CONTROLLING AUTONOMOUS DRIVING AND METHOD THEREOF - KIM DONG HYUK (2024)
An autonomous driving control device is disclosed. the autonomous driving control device may include a display unit, a sensor unit including at least one sensor, a memory, and a control unit. for example, the autonomous driving control device may obtain state information of a user using the sensor unit while controlling a subject vehicle based on a designated autonomous driving mode, determine whether the state information satisfies a designated condition, and when the state information satisfies the designated condition, use the display unit to provide the user with a user interface for switching control over the subject vehicle. 자율 주행 제어 장치가 개시된다, 자율 주행 제어 장치는, 표시부, 적어도 하나의 센서를 포함하는 센서부, 메모리, 및 제어부를 포함할 수 있다. 예를 들어, 자율 주행 제어 장치는, 자차량을 지정된 자율 주행 모드에 기반하여 제어하는 동안에, 센서부를 이용하여 사용자의 상태 정보를 획득하고, 상태 정보가 지정된 조건을 만족하는지 여부를 판단하고, 상태 정보가 지정된 조건을 만족하는 경우, 표시부를 이용하여 자차량에 대한 제어권의 전환에 관한 유저 인터페이스를 사용자에게 제공할 수 있다.